PERIPHERAL OSSIFYING FIBROMA OF MANDIBLE IN A FEMALE PATIENT REPORT OF A CASE - Gorantla, Deepika; SVVS Musalaiah; Pavuluri Aravind Kumar; Narendra Babu M; Kalapala Raviraj; Harish Prabhudev (Journal of Biomedical and Pharmaceutical Research, 2020)
Fibrous growths in the gingiva with the histopathological presence of calcifications are a common occurrence in the oral cavity. These lesions can be neoplastic in nature with either odontogenic or non odontogenic origin or they can be reactive lesions. Peripheral ossifying fibroma (POF) is one of the inflammatory reactive hyperplasia of gingiva. It represents a separate clinical entity rather than a transitional form of pyogenic granuloma and shares unique clinical characteristics and diverse histopathological features. Here, we present a case report of peripheral ossifying fibroma (POF) in an adult female in her fourth decade of life. This case report comprises the growth that occurred in the mandibular posterior region. POF in the age of 45 years, arising in the mandibular posterior region, is an occasional entity. Careful clinical examination and histopathology findings should be correlated to conclude the final diagnosis.